(3GdebGdI aj GdQO Ydi GdefLejfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3Ydi GdHGQ GdefRg Yf GdMO hGdYOe JhcdJ hHGdgGOi GdbGFe EYJUeJ hJhSdJ bGd GdYHO GdebJfi GdeeJMf HaQGYfg GdOjf s
(3BNQgG (B:s
(3hGdMeO ddehdi GdEdg GdMGce GdefRg Yf GdaYd hGdUaI JeJ Hefg hdi GdCeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B84s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds